Sistema de triagem e agendamento aplicado ao atendimento cível da defensoria pública de Tucuruí - PÓ, Adrian Caldas (2025)
This work presents the development of an automated system for civil service in the Public Defender's Office of Tucuruí, aiming to modernize and optimize the scheduling and triage processes. The initiative arose from an analysis of the previously used manual method, which relied on Microsoft Word tables, revealing limitations in terms of efficiency and data management security. To overcome these challenges, the creation of a robust and scalable system was proposed, using technologies such as Node.js integrated with MySQL Workbench. The development was guided by software engineering methods, including a detailed requirements analysis to ensure the system met the specific needs of the Public Defender's Office. The implementation resulted in an automated system capable of securely and efficiently storing and processing data, eliminating the risks associated with the manual process. Additionally, the system offers an intuitive interface, enhancing ease of use for the staff responsible for triage and scheduling activities. After implementation, tests were conducted to assess the system's performance and acceptance by end users. The results demonstrated a positive reception by the staff, who highlighted improvements in organization and process efficiency. Therefore, the project not only addresses the limitations of the previous method but also establishes a technological foundation that can be expanded to meet other institutional demands, promoting greater efficiency and reliability.